Significant Difference in Antimicrobial Resistance of Bacteria in Septic Revision between Total Knee Arthroplasty and Total Hip Arthroplasty - Stella Stevoska; Felix Himmelbauer; Julian Stiftinger; Christian Stadler; Lorenz Pisecky; Tobias Gotterbarm; Antonio Klasan (MDPI AG, 2022)
Antimicrobial resistance (AMR) aggravates the already difficult treatment of periprosthetic joint infections (PJI). Due to many factors influencing AMR, the correct choice of antimicrobial management remains arguable. The primary purpose of this retrospective study was to identify and compare bacteria and their antibiotic resistance profile between septic revision total knee arthroplasty (TKA) and septic revision total hip arthroplasty (THA). A review of all revision TKAs and revision THAs, undertaken between 2007 and 2020 in a tertiary referral hospital, was performed. Included were cases meeting the consensus criteria for PJI, in which an organism has been identified. There were no major differences in tissue sampling between revision TKAs and revision THAs over time. A total of 228 bacterial strains, isolated after revision TKA and THA, were analysed for their resistance to 20 different antibiotics. There was a statistically significant higher occurrence of Gram-negative bacteria identified after revision THAs compared to TKA (p = 0.002). The comparison of antibiotic resistance between revision TKAs and revision THAs was statistically significant in 9 of 20 analysed antibiotics. This has implications for the choice of empirical antibiotic in revision surgery as well as prophylactic antibiotic in primary surgery, depending on the joint that is to be replaced.